Stability conditions for refractive partially integrable piecewise smooth vector fields - Buzzi, Claudio A. [UNESP]; Rodero, Ana Livia [UNESP]; Teixeira, Marco A. (Elsevier, 2022)
In this article we discuss some qualitative and geometric aspects of non-smooth dynamical systems theory. Our main goal is to study stability problems inside the class of 3−dimensional refractive piecewise smooth vector fields. Our concern is to study refractive vector fields that admit a first integral that leaves invariant any sphere centered at the origin. Global stability conditions on generic one-parameter families of refractive piecewise smooth vector fields on a two-dimensional sphere are presented and used to prove our main result, which establishes necessary conditions for the structural stability inside that class.
Keywords: Integrability; Peixoto's theorem; Refractive piecewise smooth vector fields; Structural stability